1995
DOI: 10.1080/09595239500185551
|View full text |Cite
|
Sign up to set email alerts
|

SEMINARS IN PRACTICAL MANAGEMENT: “Riding the Tiger”: lessons from a health promotion activity aimed at reducing the use of alcohol by youth

Abstract: This paper outlines a health promotion activity entitled "Riding the Tiger". "Riding the Tiger" aims to reduce binge drinking among youth and is an applicable intervention for both rural and urban areas. The paper aims to provide health care workers wishing to reduce the binge drinking of youth with a practical guide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Evaluation results showed that many students positively evaluated the messages; however, some students responded negatively as a result of psychological reactance (Ricciardelli and McCabe, 2008). Similar campaigns, such as Rutgers University's “RU SURE Campaign” (Lederman and Stewart, 2005; Lederman et al , 2001), University of Mississippi's anti‐drinking campaign (Gomberg et al , 2001), University of Arizona's campaign to reduce binge drinking (Glider et al , 2001), the social norms marketing campaign (DeJong et al , 2006), the “Riding the tiger” campaign (Pokinghorne and Gill, 1995), and the “Done 4” campaign (Russell et al , 2005), led, in general, to positive results. For example, the media campaign implemented at the University of Arizona, which employed advertisements, non‐alcohol activities, leaflets, and displays at events, had reportedly led to a 29.2 percent decrease in binge drinking rates over a three‐year period (Glider et al , 2001).…”
Section: Social Marketing and Underage Drinkingmentioning
confidence: 99%
“…Evaluation results showed that many students positively evaluated the messages; however, some students responded negatively as a result of psychological reactance (Ricciardelli and McCabe, 2008). Similar campaigns, such as Rutgers University's “RU SURE Campaign” (Lederman and Stewart, 2005; Lederman et al , 2001), University of Mississippi's anti‐drinking campaign (Gomberg et al , 2001), University of Arizona's campaign to reduce binge drinking (Glider et al , 2001), the social norms marketing campaign (DeJong et al , 2006), the “Riding the tiger” campaign (Pokinghorne and Gill, 1995), and the “Done 4” campaign (Russell et al , 2005), led, in general, to positive results. For example, the media campaign implemented at the University of Arizona, which employed advertisements, non‐alcohol activities, leaflets, and displays at events, had reportedly led to a 29.2 percent decrease in binge drinking rates over a three‐year period (Glider et al , 2001).…”
Section: Social Marketing and Underage Drinkingmentioning
confidence: 99%